The Dynamics of Enforcement of State Administrative Law through the PTUN in Realizing Good Governance in Indonesia - Khairunnisa Siregar; Livia Maylisandi (AT-TAFAHUM: Journal of Law, 2020)
The enforcement of state administrative law (PTUN) is a crucial element in realizing good governance and ensuring the implementation of the principles of the rule of law as mandated by the 1945 Constitution. This study aims to analyze in depth the concept of PTUN, its implementation mechanisms, factors that influence its effectiveness, as well as obstacles and innovative solutions in the Indonesian context. A normative juridical approach is used by reviewing legal literature, laws and regulations such as Law No. 30 of 2014 concerning State Administration and Law No. 5 of 1986 concerning PTUN (as amended), as well as state administrative law doctrine. The results of the study reveal that PTUN is not limited to the imposition of administrative sanctions alone, but includes preventive dimensions (prevention through education), corrective (improvement of procedures), and repressive (action through the courts). The main mechanisms include the application of general principles of good governance (AUPB) such as legality, proportionality, and legitimate trust, the legitimate use of discretionary authority, orderly administrative procedures, and legal remedies through the State Administrative Court (PTUN) and supervisory institutions such as the Ombudsman. However, in practice, these challenges face serious obstacles, such as low legal awareness among state civil servants (ASN) and the public, overlapping regulations between laws, a weak internal-external oversight system, and structural corruption that undermines institutional independence. External factors such as disparities in regional resources also exacerbate the situation. Therefore, strategic solutions are proposed in the form of regulatory harmonization through revisions to the omnibus law, increasing ASN professionalism through ongoing training, transparency in public services through digital platforms, and strengthening the role of civil society and the media in participatory oversight. With this implementation, the PTUN is expected to create a transparent, accountable, responsive, and just government, in line with the vision of Golden Indonesia 2045.